2009
DOI: 10.1159/000212385
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Inhibition after Glucocorticoid Exposure in Healthy Men with Low versus High Basal Cortisol Levels

Abstract: Objective: The balance between glucocorticoid (GC) release and GC sensitivity in target cells is believed to be important to maintain homeostasis in the neuroendocrine control of inflammation. We investigated the impact of in vivo exposure to adrenocorticotropic hormone (ACTH) and dexamethasone (DEX) on GC sensitivity measured in vitro in healthy individuals with high versus low baseline cortisol levels. Methods:136 healthy male volunteers were screened twice and sorted according to their 24-hour urinary free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Lekander and co-workers reported low cortisol individuals defined as above, to display a weaker inhibition of IL-6 after a low dose Dexamethasone treatment compared to high cortisol individuals, thus being more sensitive to prolonged glucocorticoid exposure [186]. These results are in accordance to our findings described in paper IV.…”
Section: Paper IVsupporting
confidence: 92%
“…Lekander and co-workers reported low cortisol individuals defined as above, to display a weaker inhibition of IL-6 after a low dose Dexamethasone treatment compared to high cortisol individuals, thus being more sensitive to prolonged glucocorticoid exposure [186]. These results are in accordance to our findings described in paper IV.…”
Section: Paper IVsupporting
confidence: 92%
“…Previous studies showed that administration of DEX inhibited lipopolysaccharide (LPS)-stiumulated production of IL-1β [55,56], suggesting that DEX may affect the function of IL-1β gene. Therefore, future studies should examine the influence of IL-1β gene polymorphisms on not only basal IL-1β levels but also DEX-induced IL-1β levels.…”
Section: Discussionmentioning
confidence: 99%
“…In human volunteers, a 2 week administration of dexamethasone (a synthetic GC) resulted in an attenuation of GC mediated inhibition of IL-6 and TNF-alpha production in vitro [39]. Further, experimentally increased plasma cortisol levels (concentrations of 75 to 85 µg/dL for a 6-hr period) ending 12–144 hours before injection of endotoxin, resulted in an increased proinflammatory response to the bacterial product[13].…”
Section: Introductionmentioning
confidence: 99%